Households' Food Insecurity and Their Association With Dietary Intakes, Nutrition-Related Knowledge, Attitudes and Practices Among Under-five Children in Gaza Strip, Palestine - El Bilbeisi, Abdel Hamid; Al-Jawaldeh, Ayoub; Albelbeisi, Ali; Abuzerr, Samer; Elmadfa, Ibrahim; Nasreddine, Lara (Frontiers in Public Health, 2022)
The present study aimed to determine the households' food insecurity and their association with dietary intakes, nutrition-related knowledge, attitudes and practices (KAP) among under-five children in the Gaza Strip, Palestine. This cross-sectional study was conducted in 2021 among a representative sample of under-five children. A total of 350 children and their proxy were selected from all Gaza strip governorates, using a cluster random sampling method. The Radimer/Cornell food-security scale was used. A 24-h dietary recall was employed for dietary intakes assessment. Nutrition-related KAP for feeding under-five children, anthropometric measurements, and demographic-socioeconomic characteristics were obtained with an interview-based questionnaire. Statistical analysis was performed using SPSS version 25. The children from food-insecure households had a high prevalence of moderate underweight (30.4%), stunting (32.8%), wasting (9.6%), and acute undernutrition (30.4%). Between food-insecure and food-secure groups there were significant differences in weight, height/length, mid-upper arm circumference, weight-for-age and mid-upper arm circumference z-scores, underweight, acute undernutrition, intakes of protein, fat, vitamin D, zinc, continued breastfeeding, having nutrition-related adequate knowledge, having nutrition-related positive attitudes, and achieved minimum dietary diversity score (P < 0.05 for all). Additionally, about (56.0%) food-insecure households have inadequate nutrition-related knowledge, (77.6%) have nutrition-related negative attitudes, and (95.2%) did not achieve a minimum dietary diversity score. In conclusion, the children from food-insecure households had a high prevalence of moderate underweight, stunting, wasting, and acute undernutrition. Moreover, low economic status, poor dietary intakes, low levels of nutrition-related KAP, and lack of dietary diversity could contribute to the high levels of food insecurity among under-five children.